ISLAMIC CHARACTER EDUCATION THROUGH LEARNING AQIDAH AKHLAK (STUDY ON 7TH GRADE STUDENTS AT SMP MUHAMMADIYAH 8 SURAKARTA) - Khotimah, Dewi Fitriah Khusnul; Hafidz, H (Proceeding of International Conference of Islamic Education, 2024)
This study describes Islamic character education through learning aqidah akhlak. This study aims to reveal the strategy of Islamic character education in learning aqidah akhlak, how to build student character in learning aqidah akhlak, and what are the obstacles in the application of Islamic character education in learning aqidah akhlak for regular grade 7 students at SMP Muhammadiyah 8 Surakarta. Data collection using observation and interview techniques. This data processing uses qualitative techniques. This technique is used to process data from observations and interviews. The results showed that the Islamic character education strategy in learning Aqidah Akhlak in students is a conscious effort from teachers to instill and form Islamic character. Lack of parental attention is also an inhibiting factor in the development of character education because they are busy with various kinds of work.